Associations between Manual Abilities, Gross Motor Function, Epilepsy, and Mental Capacity in Children with Cerebral Palsy - GAJEWSKA, Ewa (Shahid Beheshti University of Medical Sciences, 2014)
OBJECTIVE: This study aimed to evaluate gross motor function and hand function in children with cerebral palsy to explore their association with epilepsy and mental capacity. MATERIAL & METHODS: The research investigating the association between gross and fine motor function and the presence of epilepsy and/or mental impairment was conducted on a group of 83 children (45 girls, 38 boys). Among them, 41 were diagnosed with quadriplegia, 14 hemiplegia, 18 diplegia, 7 mixed form, and 3 athetosis. A neurologist assessed each child in terms of possible epilepsy and confirmed diagnosis in 35 children. A psychologist assessed the mental level (according to Wechsler) and found 13 children within intellectual norm, 3 children with mild mental impairment, 18 with moderate, 27 with severe, and 22 with profound. Children were then classified based on Gross Motor Function Classification System and Manual Ability Classification Scale. RESULTS: The gross motor function and manual performance were analysed in relation to mental impairment and the presence of epilepsy. Epilepsy was found to disturb conscious motor functions, but also higher degree of mental impairment was observed in children with epilepsy. CONCLUSION: The occurrence of epilepsy in children with cerebral palsy is associated with worse manual function. The occurrence of epilepsy is associated with limitations in conscious motor functions. There is an association between epilepsy in children with cerebral palsy and the degree of mental impairment. The occurrence of epilepsy, mainly in children with hemiplegia and diplegia is associated with worse mental capacities.